Studi komparatif usahatani kopi robusta=A Comparative Study on Organic with Non Organic Robusta Coffee in Samigaluh Subdistrict ofKulon Progo Regency - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
Most of the coffee production in Indonesia was still on small-scale farm with low productivity. To increase farmers' income, the government tried to establish a cooperation with PT Sarana Yogya Ventura (PT SYV) through a livestock diversification of Ettawa goat that could be used as a base capital in implementing organic coffee cultivation. This research was aimed to know the factors influencing on and the problems on organic and non organic robusta coffee farming. The study was carried out in Kulon Progo Regency that had been the center of robusta coffee in cooperation with PT SYV. Data was collected from 50 farmers of organic coffee and 50 farmers of non organic coffee by using simplified random sample method. The analysis used was a Cobb-Douglass production function and of two means. The results showed that the factors influencing organic robusta coffee production were manure, labor, plant population, and cutting. On the other hand, the factors influencing on non organic robusta production were manure, urea based fertilizer, SP-36, labor, and cutting. The production of organic and non organic robusta coffee were diferent, meaning that the cooperation program could increase the farmers'r income.